PENGARUH PEMBERIAN MINYAK IKAN GINDARA (Lepidocybium flavobrunneum) TERHADAP KADAR KOLESTEROL HDL TIKUS PUTIH HIPERKOLESTEROLEMIA - Siti Fatimah; Mia Lisna Andriani; Leo Gusti Agata (Jurnal Penelitian Sekolah Tinggi Ilmu Kesehatan Nahdlatul Ulama Tuban, 2020)
Gindara fish oil contains several active ingredients that are thought to increase HDL cholesterol levels in the blood. The increase in HDL cholesterol levels is caused by gindara fish oil containing ɷ-3, ɷ-6, and ɷ-9. Gindara fish oil content is around 12-20% of body weight. A study was conducted to determine the effect of Gindara fish oil (Lepidocybium flavobrunneum) on HDL cholesterol levels in hypercholesterolemic white mice fed high-fat feed. This research was conducted experimentally using 25 male white rats (Rattus novergicus, L.), aged 2-3 months with a weight of 150-200 g, which were divided into 5 random treatment groups, namely the K1 group (normal control) were fed standard, the K2 group (positive control) was given high-fat feed for 7 days, while the P1, P2, and P3 groups were given orally gindara fish oil at a dose of 54mg / 200gBB / day, 108mg / 200gBB / day, 216mg / 200g BW / day. Each treatment consisted of 5 mice which were examined 3 times the HDL cholesterol level by the CHOD-PAP method. Data obtained from the examination were analyzed using the Crucial Wallis test p <0.05 followed by a post hoct test. with Mann-Whitney. Research Results P1, P2, and P3 groups were significantly different from K1 (p = 0.008). Groups P1, P2, and P3 were significantly different from K2 (p = 0.008). Gindara fish oil with a dose of 54mg / 200g BW / day, 108mg / 200g BW / day, 216mg / 200g BW / day each can increase HDL cholesterol levels by 38% or 15.09 mg / dl, 50% or 25.92 mg / dl, and 59% or 34.51 mg / dl.